Penerapan Model Problem Based Learning (PBL) dan Media Wordwall untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas II Sekolah Dasar - Riska Nurul Latifah; Ahmad Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve mathematics learning outcomes of second-grade elementary school students through the implementation of the Problem Based Learning (PBL) model supported by Wordwall media. The problem addressed in this research is the low achievement of students in the topic of length measurement. This research employed a Classroom Action Research (CAR) method conducted in two cycles. The research subjects consisted of 34 second-grade students. Each cycle included the stages of planning, action, observation, and reflection. The primary instrument used was a multiple-choice test consisting of 10 questions. The results showed that the implementation of PBL with Wordwall media effectively improved students' mathematics learning outcomes. In the pre-cycle, only 8 students (23.53%) met the Learning Objectives Achievement Criteria (KKTP) with an average score of 55.82. In the first cycle, the number of students who achieved mastery increased to 18 (52.94%) with an average score of 68.91. In the second cycle, 28 students (82.35%) achieved mastery with an average score of 78.65. The use of the PBL model combined with Wordwall media proved effective in creating meaningful and interactive learning, enhancing students’ understanding of length measurement concepts.